Edukasi deteksi dini kanker payudara dan serviks berbasis komunitas pada Muslimat NWDI - Ero Ari Angga; Arief Rahman; Andi Nizam Harahap; Intan Nefia Alamanda; Lalu Ramadlan; Raani Amaani; Faradila Faradila; Hartini Haritani (Universitas Hamzanwadi, 2025)
Cancer education is an essential effort to improve public awareness and understanding, particularly among women, regarding the early detection of breast and cervical cancer. This community service activity aimed to provide education on cancer awareness, the importance of early detection, and the adoption of healthy lifestyles among Muslimat NWDI in East Lombok, West Nusa Tenggara. The activity was conducted through health education sessions combined with interactive discussions and an evaluation of participants’ understanding using a simple assessment instrument. The educational materials covered an introduction to breast and cervical cancer, breast self-examination (BSE), the importance of Pap smear screening, and lifestyle-related factors associated with cancer prevention. The results indicated that most participants demonstrated good to very good levels of understanding of the presented materials. Higher levels of understanding were observed among pre-elderly participants and those with a higher educational background. However, psychosocial barriers such as feelings of shame, fear, and cultural stigma related to reproductive health examinations were still identified. This socialization activity contributed positively to increasing participants’ awareness of the importance of early cancer detection. Nevertheless, continuous assistance and improved access to health services are needed to ensure the practical implementation of early detection behaviors within the community